Grief and Bereavement in the Latino/a Community: A Literature Synthesis and Directions for Future Research (Mary Ann Liebert, 2022)
Introduction: Bereavement and grief are social phenomena influenced by a multitude of cultural factors. Prior studies of bereavement adjustment have primarily focused on bereaved survivors who identify racially as white; knowledge of the experience of grief and bereavement among racial/ethnic and other minority groups, particularly among Latino/a groups, in the United States is limited. Objective: The purpose of this review is to synthesize the literature documenting the bereavement experiences of the Latino/a community, evaluate the strength of the current evidence, and provide recommendations to guide future research. Method: A narrative review of research on grief and bereavement in the Latino/a community published between 1990 and 2021. Two authors used a thematic, deductive approach to categorize emergent prevalent themes from the literature and used The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) and The Oxford Center for Evidence-Based Medicine?Evidence Quality Rating Scale (OCEBM) approaches to evaluate the strength of the qualitative and quantitative reports reviewed. Results: Searches revealed 26 reports that were categorized into six themes: cultural values, mourning rituals, immigration, spirituality, disparities related to the COVID-19 pandemic, and the effects of COVID-19 on Latino/a communities. Our evaluation concludes that the evidence in this area is weak, with limited methodologically rigorous research examining the influence of culture on bereavement among Latino/a groups. Conclusion: Research is needed to identify Latino/a groups' mental health, cultural, social, and family needs and how fulfillment of mourning rituals and other cultural factors may promote or impede bereavement adjustment. Investigation into factors that may protect bereaved survivors against adverse mental health outcomes is also needed. A better understanding of Latino/a grief and bereavement is a step toward the development of culturally competent interventions designed to promote the mental health and psychosocial adjustment of Latino/a mourners.